Intertwining nutrient‐sensory networks and the control of antibiotic production in Streptomyces. Issue 2 (9th August 2016) - Urem, Mia; Świątek‐Połatyńska, Magdalena A.; Rigali, Sébastien; van Wezel, Gilles P.
Summary: Actinobacteria are producers of a plethora of natural products of agricultural, biotechnological and clinical importance. In an era where mankind has to deal with rapidly spreading antimicrobial resistance, streptomycetes are of particular importance as producers of half of all antibiotics used in the clinic. Genome sequencing efforts revealed that their capacity as antibiotic producers has been underestimated, in particular as many biosynthetic pathways are silent under standard laboratory conditions. Here we review the global regulatory networks that control antibiotic production in streptomycetes, with emphasis on carbon‐ and aminosugar‐related nutrient sensory pathways. Recent research has revealed intriguing connections between these regulons, and overlap and antagonism between the activities of among others the global regulatory proteins AtrA, DasR and Rok7B7 as well as GlnR (nitrogen control) and PhoP (phosphate control), are discussed. Finally, we provide ideas as to how these novel insights might help us to find ways to activate the transcription of silent biosynthetic gene clusters. Abstract : Streptomycetes are prolific producers of antibiotics and other natural products, but many biosynthetic gene clusters are silent under standard laboratory conditions. In this review, we look into the global nutrient sensory networks that control antibiotic biosynthetic pathways in Streptomyces, and highlight cross‐talk between different pleiotropic regulators. Approaches to harness this information to activate the production of silent antibiotics are discussed.